Implementación de un nuevo tipo penal de violación a la intimidad e integridad sexual en el régimen penal ecuatoriano - Merchán Armijos, Leidy Geanella (2022)
The general objective of this curricular integration work is to analyze the incidence of Covid-19, pre and post economic-financial results in microenterprises in the canton Puyango - Alamor, in the periods 2018-2021. In order to identify the economic sectors most affected by the pandemic, microenterprises in the Puyango-Alamor canton were taken as the object of study, using the database obtained through the Internal Revenue Service (SRI) (Annex 3), determining a population of 722 microenterprises in the sector, obtaining a probabilistic sample of 251 to whom a survey was applied directed to their representatives in order to obtain information that helps to know the economic-financial situation they went through in the period in question. Once the results were obtained, it was determined that in the microenterprises of the Puyango-Alamor canton, the sector that generates the greatest income is the tertiary sector, which includes commerce and services activities, with a total of $ 21,805,707.90, followed by the primary sector corresponding to agriculture, livestock, forestry and fishing, with a value of $ 15,849,139.48, in the periods analyzed. The secondary sector, that is, the manufacturing and construction industries, presented the least income, with an amount of $912,980.90, thus establishing that the Covid-19 pandemic affected the income and expenses of all microenterprises. In addition, a general report was prepared for the microenterprises in the area, containing conclusions and recommendations, with a view to these becoming a tool to assist in future decision-making and economic reactivation of the affected sectors.